2011
DOI: 10.1055/s-0031-1280878
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Patellofemoral Impingement: A Cause of Treatable Pain after TKA

Abstract: Multiple etiologies may cause anterior knee pain after total knee arthroplasty. While prior studies have addressed component positioning and surgical technique, no series in the literature describes lateral patellofemoral impingement as a source of the pain. Over a 2-year period at our institution, 18 patients with 19 painful total knee arthroplasties were diagnosed with lateral patellofemoral impingement. All underwent revision surgery with either lateral facetectomy or revision of the patellar dome. These pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Rotational alignment of the tibial and femoral components is an important factor influencing patellar tracking. A malpositioned femoral component increases the patellofemoral contact pressure, thus affecting the clinical outcome and the long-term survivorship of the implant [6,12]. However, in patients with persistent AKP after TKA, the source of symptoms cannot be identified [2,3,14].…”
Section: Introductionmentioning
confidence: 99%
“…Rotational alignment of the tibial and femoral components is an important factor influencing patellar tracking. A malpositioned femoral component increases the patellofemoral contact pressure, thus affecting the clinical outcome and the long-term survivorship of the implant [6,12]. However, in patients with persistent AKP after TKA, the source of symptoms cannot be identified [2,3,14].…”
Section: Introductionmentioning
confidence: 99%
“…9 Similarly, Cercek et al reported 19 knees diagnosed with LPFI that underwent LPF in 15 knees and revision of the patellar component in 4 knees, and their symptoms were improved. 12 Pagenstert et al compared the clinical and radiological results of secondary patellar resurfacing with and without LPF for lateral facet syndrome after patellar nonresurfaced TKA. They reported that better clinical results and improved patellar tilt were obtained in the LPF group.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,12 Lateral patellar facetectomy (LPF) that resects the lateral aspect of the patella that caused the impingement is an effective method of treating LPFI, as is revision of the patellar component. 9,12 In addition, LPF has been reported to reduce patellofemoral joint pressure and is one of the treatment options for patellofemoral osteoarthritis. 13,14 The application of LPF in primary TKA is expected to lead to better clinical outcomes, including a reduced incidence of AKP.…”
mentioning
confidence: 99%
“…Additional indications for arthroscopic lateral patellar facetectomy could be treatment of residual or recurrent osteophytes 19 or patellofemoral impingement in patients post-total knee arthroplasty (TKA) with patellar resurfacing, presenting with excessive lateral patellar tilt. 20 Furthermore, arthroscopic lateral patellar facetectomy could be used in the setting of painful lateral patellofemoral OA after TKA without prosthetic patella resurfacing to treat impingement between the lateral facet and the femoral implant. 21 As evidenced by these 3 studies, 19 , 21 , 22 lateral patellar facetectomy in patients post-TKA has been shown to improve patellar tilt and lateral patellar displacement for both resurfaced and nonresurfaced patellae.…”
Section: Discussionmentioning
confidence: 99%